Fungsi Karang Taruna Dalam Memberdayakan Pemuda Desa Parangina Kecamatan Sape Kabupaten Bima - Wawan Mulyawan (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Karang Taruna as a forum for community participation in fostering and developing the younger generation is in a strategic position, and is a vehicle that can play an active role in the development process in the kelurahan. On the one hand, Karang Taruna can be seen as a potential subject of development in the kelurahan; on the other hand, Karang Taruna can be seen as an object of development, which is a strategic target of the process of implementing development in the kelurahan. In the process of strategic existence, the function and role of Youth Organization can be optimized to become an efficient and effective development subsystem. Consequently, it is necessary to optimize, quality, and effectiveness of the role of Youth Organization in the development of the younger generation in particular and is expected to contribute to every dimension of development at a macro level. Because in accordance with its nature, Karang Taruna is a youth social organization, a forum for the activities of young people in villages and sub-districts to develop themselves and build their communities. Karang Taruna is one of the community's social self-help forces that can direct and mobilize the potential of the younger generation to participate in spurring development activities in their environment.